Analyzing external drivers of early education TVET adoption in Malaysia: Implications for vocational education policy and practice - Musa, Haslinda; Abdullah, Abdul Rahim; A Khadar, Nur Zafirah; Othman, Mohd Nasar; Azmi, Fadhlur Rahim (Research and Scientific Innovation Society, 2025)
In most developed countries, Technical and Vocational Education and Training (TVET) system is considered as one of the key factors in promoting industrial growth through the development of a competent and skilled workforce. With the increasing importance of early education in preparing young learners for their future careers, TVET programs have gained attention for their potential to provide practical skills and knowledge to children at an early stage. This study aims to investigate the external factors that influence the adoption of Technical and Vocational Education and Training (TVET) in early education in Malaysia. Understanding external factors and their perceptions of TVET adoption is critical to designing effective educational strategies and facilitating their successful implementation. This study uses a quantitative survey as the research method. Higher education participants, parents and teachers in Malacca, Malaysia will be selected as the sample to participate in this study. The results of the study will provide insight into the factors that contribute to the acceptance or resistance to early education TVET in Malaysia. Thus, it is expected that this study will provide upcoming academic scholars with a reliable and accurate grasp of TVET early education. By understanding the external factors, policy makers can design targeted interventions and strategies to effectively promote the adoption of TVET programs.